(3GdYUeI Yf GdVdGds - (3GdMSf Hf CMeO GdLdGds ((3eMeO Hf ESeGYjd GdCejQ s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg GdEYGfg hYdjg GdJhcd ai GdHOGjI hHYO agPg fHPg Led ef CUhd GdNdGa ai GdYbGFO hSejJgG GdYUeI Yf GdVdGd s
(3BNQgG (B:s
(3hHELeGY GdUMGHI Ydi bJGd eG fYi GdRcGg ai ebGHdI Jdc GdbhGWY ghS dG ELJgGO gPG eG CQOfG LeYg ef CUhd GdYbGFO hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HChdgG fbhd hJYdjbGJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs